THE PHAEOSPHAERIA LEAF SPOT OF MAIZE IN BRAZIL: EVIDENCES OF A NEW ETHIOLOGIC AGENT - OLIVEIRA, ELIZABETH DE; FERNANDES, FERNANDO TAVARES; CARVALHO, ENIA MARA; MACHADO, JOSÉ DA CRUZ (International Journal of Maize & Sorghum, 2010)
“Phaeosphaeria leaf spot of maize” is a common and very important disease in Brazil. This disease was first described in India, and it was assumed to be caused by the fungus Phaeosphaeria maydis f. imp. Phyllosticta sp. However, in Brazil, several inoculations of this fungus in maize have not been successful on symptom developing. In addition, characteristic structures of P. maydis or Phyllosticta, perithecia or picnidia, respectively, are hardly seen on lesions of that disease. Eighty samples of “Phaeosphaeria leaf spot of maize” were collected between September 2000 and February 2004 and analyzed by scanning electron microscopy to check fungal structures presence. The lesions were also analyzed under light microscopy, and by transmission electron microscopy. In some cases, diseased leaf fragments were incubated on PDA medium or water-agar to observe growth of the isolated fungi. P. maydis or Phyllosticta sp perithecia or picnidia, respectively, were never found in the analyzed samples. A very thin hyphae (diameter less than 2μm) and small structures identified as sporangia (23,9μm diam.), zoosporos (3,2-3,5μm x 1,7–2,0μm) and oocito (10,4μm – 12,5μm diam.) were present in 100% of the examined lesions. Based on those facts and considering that the fungus did not grow on PDA medium, making the application of Koch’s Postulates difficult, the possibility of such fungus to be considered the ethiologic agent of that disease is quite high. Apparently, this fungus is a new species in Peronosporaceae, possibly genus Sclerophthora. However, confirmation of that hypothesis requires the development of additional studies.